Report on the socioeconomic, humanitarian and human rights situation in the PalmaAfungi-Mocímboa area (Cabo Delgado) - Rufin, Jean-Christophe; Glowacki, Ingrid (Total Energies, 2023)
Patrick Pouyanné, Chairman and CEO of TotalEnergies, entrusted Jean-Christophe Rufin in December 2022, on behalf of the partners of the Mozambique LNG project, with an independent mission to assess the humanitarian situation in the province of Cabo Delgado where the project is located. Jean-Christophe Rufin, a recognized expert in the field humanitarian action and human rights, has carried out several investigation field trips in Mozambique. TotalEnergies publishes his report as well as the action plan decided by Mozambique LNG partners based on the recommendations of the report. The report recalls that the conflict in the province of Cabo Delgado has origins pre-dating the gas development projects and finds its roots in multiple factors not related to Mozambique LNG. It assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. The report assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. It notes an improved humanitarian situation in the north of Cabo Delgado, in particular with the return of the populations displaced by the conflict to the town of Palma and to a lesser degree to the town of Mocímboa da Praia. The report highlights the execution quality of the actions undertaken by Mozambique LNG and their positive impact on the living conditions of local population. However it recommends the establishment of a dedicated structure with increased resources to further expand these programs and to integrate them into an ambitious and sustainable strategy of local development covering the whole province, and not only guided by the security of the project site. Regarding the populations affected by the development of the Afungi industrial site, Jean-Christophe Rufin recommends several avenues of improvements to finalize in the best conditions the implementation of the resettlement plan and ensure the compensation of affected persons in accordance with the best practices. These improvements relate in particular to the update of the inventories of the affected persons’ assets, the payment timeline of compensations, the provision of agricultural land and the access to fishing areas.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; conflict / conflito; displaced communities / comunidades deslocadas; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; infrastructure - energy / infrastrutura - energia; natural resources - gas / recursos naturais - gás; private sector / setor privado; security / segurança; social action / ação social

Os espaços de participação e de exercício da cidadania, na voz de líderes associativos da província de Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
O texto descreve os obstáculos históricos ao desenvolvimento de organizações da sociedade civil (OSC) em Moçambique, que conheceram um cenário mais acolhedor na Constituição de 1990. Mecanismos de apoio à sociedade civil capacitaram líderes locais, tornando-os melhor conhecedores de dispositivos legais, capazes de reunir evidências e de exercer impacto junto das populações. Contudo, as organizações enfrentaram problemas internos, relacionados com a ausência de recursos financeiros, com a capacitação dos seus membros e com problemas de transparência e rotatividade. O sistema de ensino desenvolve poucas competências de cidadania activa e o Estado desconfia de iniciativas de consciencialização das populações em direitos fundamentais ou em mecanismos de participação cívica. A manutenção de uma cultura política de súbdito foi funcional à penetração do grande capital na exploração de recursos naturais. As OSC enfrentam obstáculos à participação, relacionados com a forte politização da sociedade, com a desconfiança governamental em relação ao escrutínio público, proibição de manifestações públicas e receio das suas lideranças, particularmente após o início do conflito armado. A proliferação de conflitos nas áreas da indústria extractiva e a inexistência de canais formais de participação e de acesso à justiça foram agudizaram tensões, habilmente capitalizadas por grupos violentos. A guerra dispersou os membros de OSC que timidamente floresciam nos vários distritos, retirando-lhes capacidade organizativa, de advocacia e pressão social. A chegada de organizações humanitárias internacionais em resposta à emergência pouco incluiu as associações locais, reproduzindo relações assistencialistas e de dependência. O texto demonstra a urgência de identificação de líderes locais, (re)capacitação das OSC e criação de fóruns de participação social, invertendo a crença de que a violência constitui a forma possível e legítima de participação.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - portuguese / português; authority / autoridade; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; governance / governação

Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Descolonizar os estudos urbanos em África. Conflitos armados e sustentabilidade urbana em Cabo Delgado. - Amaral, Silvia (Desafios para Moçambique 2022, 2022)
Este projecto de investigação pretende, assim, humildemente, contribuir para a descolonização dos estudos urbanos em Moçambique e Portugal, e para a transmutação dos traumas da guerra em oportunidades de desenvolvimento sustentável e prosperidade urbana.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; conflict / conflito; politics / política

Agrarian Change in Northern Mozambique: A ‘New’ Dimension of Research in Light of the Conflict and Violence in Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Transformação Agrária No Norte De Moçambique: Uma “Nova” Dimensão De Pesquisa À Luz Do Conflito E Violência Em Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Stemming the Insurrection in Mozambique’s Cabo Delgado (International Crisis Group, 2021)
Principal Findings What’s new? Militant attacks and security force operations in Mozambique’s Cabo Delgado province have claimed nearly 3,000 lives, while displacing hundreds of thousands of people. Insecurity has prompted the suspension of a massive gas project. The Islamic State (ISIS) claims ties to the insurrection. Southern African governments are lobbying to send troops. Why did it happen? Mozambican militants have been motivated by grievances against a state that they see as delivering little for them, despite the development of major mineral and hydrocarbon deposits. Tanzanians and other foreigners have joined up, fuelling the insurrection. The country’s historically weak security forces have been unable to stem the onslaught. Why does it matter? Unaddressed, the insurrection could spread further, threatening national stability just as Mozambique is fulfilling a peace deal with the country’s main opposition group and heading into national elections in 2024. It could worsen instability along East Africa’s coast and present ISIS with a new front to exploit. What should be done? Maputo should accept targeted assistance for security operations to contain the insurrection, and avoid a heavy external deployment that could lead to a quagmire. Authorities should deploy aid to build trust with locals and open dialogue with militants. Regional governments should redouble law enforcement efforts to block transnational jihadist involvement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conter a Insurreição em Cabo Delgado, Moçambique - International Crisis Group (International Crisis Group, 2021)
O que há de novo? Os ataques de militantes e as operações das forças de segurança na província moçambicana de Cabo Delgado já custaram praticamente 3000 vidas e deslocaram centenas de milhares de pessoas. A insegurança levou à suspensão de um gigantesco projeto de gás. O Estado Islâmico (ISIS) reivindica laços com a insurreição. Os governos do Sul de Africa estão a exercer pressão para o envio de tropas. Porque aconteceu? Os militantes moçambicanos foram motivados pelo descontentamento em relação a um estado que, do seu ponto de vista, pouco fez por eles, apesar do desenvolvimento de depósitos minerais e de hidrocarbonetos significativos. Tanzanianos e outros estrangeiros juntaram-se, alimentando a insurreição. As forças de segurança, historicamente fracas, foram incapazes de conter a ofensiva. Porque importa? Se não for tratada, a insurreição pode vir a alastrar-se, ameaçando a estabilidade nacional enquanto Moçambique está a alcançar um acordo de paz com o principal grupo de oposição do país e antes das eleições nacionais de 2024. A instabilidade ao longo da costa de Africa Oriental poderia piorar e fornecer ao ISIS uma nova frente a explorar. O que deve ser feito? Maputo deveria aceitar uma assistência direcionada para suas operações de segurança, a fim de conter a insurreição, e evitar uma mobilização externa forte, que poderia levar a uma estagnação. As autoridades deveriam fornecer assistência para construir uma relação de confiança com os habitantes locais e um diálogo aberto com os militantes. Os governos regionais deveriam redobrar seus esforços em matéria de aplicação da lei para impedir a implicação jihadista transnacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; innovation / inovação

Situação humanitária em Cabo Delgado: milhares de deslocados continuam sem assistência e apoio do Governo e das agências internacionais - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Mais de 30.500 pessoas que abandonaram as suas casas devido aos ataques terroristas na vila de Palma em Março último continuam a enfrentar dificuldades de alimentação e de abrigo nos centros de acolhimento. A maioria está no centro de trânsito de Pemba e outros nos campos de deslocados de Metuge. A Matriz de Monitoria de Deslocamentos da Organização Internacional para as Migrações (OIM) continua a registar a chegada diária de deslocados que fogem da insegurança no norte de Cabo Delgado. As autoridades governamentais e as agências humanitárias interromperam, há mais de um mês, as operações de salvamento de pessoas que estão concentradas na vila de reassentamento de Quitunda, a menos de 30 quilómetros da vila de Palma. Devido à insegurança, as agências humanitárias não estão a prestar apoio a milhares de pessoas que estão em Quitunda, nas proximidades do acampamento de Afungi.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Bispo de Pemba critica Nyusi: "Se eu fosse presidente, a minha presença seria outra. Estaria a falar de Cabo Delgado todos os dias" - Castro, Pedro Jorge (Moçambique para todos, 2021)
"Como é que um corrupto pode lutar contra si mesmo? É preciso uma espécie de revolução." As ameaças do governo. A guerra. E o deslocado que disparou contra insurgentes. Entrevista ao Bispo de Pemba.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - Pemba; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado 45 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Following the rise of Islamist group al-Shabab in Cabo Delgado - Marie Toulemonde (The Africa Report.com, 2021)
A visual explanation of how Mozambique’s islamist group al-Shabab has grown over the years in the northern Cabo Delgado province.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; extractive industries / indústrias extractivas

An overview of foreign security involvement in Mozambique (defenceWeb, 2021)
A number of private security companies, foreign governments and militaries have become involved in Mozambique in its fight against the insurgency in Cabo Delgado, but the Mozambican government has so far largely limited external involvement. Nevertheless, there are a number of companies and countries providing security and security assistance to Mozambique. Private military contractors Russian […]
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Ligado 44 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Hundreds Missing After Mozambique Attack (Human Rights Watch, 2021)
Hundreds of people remain missing five days after an Islamic State (ISIS)-linked armed group known as Al-Shabab raided the town of Palma in Mozambique’s northern Cabo Delgado province, killing and wounding an unknown number of civilians and causing thousands to flee.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Cabo Ligado 43 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Cabo Ligado 42 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado 41 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

A Insurgência Jihadi em Moçambique: Origens, Natureza e Início - Morier-Genoud, Eric (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Resultante de uma investigação com trabalho de campo em Cabo Delgado em 2018 e 2019, este novo Cadernos IESE nº 21, da autoria de Eric Morier-Genoud, explica a origem, natureza, e dinâmica da guerra no norte de Moçambique com base numa análise da historicidade e das dinâmicas internas das sociedades locais. Defende o argumento segundo o qual é mais produtivo pensar nos insurgentes do Al-Shabaab em termos da sua trajectória histórica, evoluindo de uma seita islâmista para um grupo armado jihadi violento, passando actualmente por um processo de internacionalização que poderá se evoluir de várias formas no futuro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Afinal, não é só Cabo Delgado! Dinâmicas da insurgência em Nampula e Niassa - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Nos últimos três anos e meio, Moçambique enfrenta uma violência armada desencadeada por um grupo de natureza jihadista. Com origens na zona norte de Cabo Delgado e localmente conhecido pela designação Al-Shabaab, o grupo surgiu como uma seita religiosa (Morier-Genoud, 2020) e, de seguida, constituiu-se numa unidade militarizada, tendo partido para a violência armada a 5 de Outubro de 2017. Baseado em trabalho de campo nas províncias de Cabo Delgado, Nampula e Niassa, este texto procura analisar a insurgência com base em dinâmicas de alguns distritos de Nampula e Niassa. Com enfoque nos factores do avanço da insurgência no terreno, o texto sublinha o argumento, segundo o qual, a compreensão do desenvolvimento da insurgência em Cabo Delgado passa, entre outros aspectos, pela análise das dinâmicas sociais, económicas e religiosas das províncias vizinhas, nomeadamente Nampula e Niassa, que se transformaram em espaços férteis de recrutamento, particularmente a partir de 2018. O argumento é desenvolvido em dois momentos. No primeiro momento, o texto procura identificar e analisar os principais factores que conduziram ao alastramento da insurgência para mais distritos de Cabo Delgado e à tentativa de instalação de células de tendência radical em alguns distritos de Nampula e Niassa. No segundo momento, focaliza-se a atenção para as dinâmicas de recrutamento a nível interno, com destaque para alguns distritos localizados na zona costeira de Nampula e na fronteira entre a província de Niassa e a Tanzânia.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: ExxonMobil again postpones final decision on Rovuma LNG (Mozambique, 2021)
US oil company Exxon has postponed for the third consecutive year the Final Investment Decision on the natural gas exploration project in Mozambique, putting the $30 billion investment in doubt. According to Bloomberg news agency, which quotes the company's Senior Vice President Neil Chapman, Nei
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

O que vi foi a morte: crimes de guerra no "cabo esqueçido" de Moçambique (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

What I saw is death: War crimes in Mozambique's forgotten cape (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Mozambique: Civilians killed as war crimes committed by armed group, government forces, and private military contractors – new report (2021)
The new report documents serious violations of international humanitarian law by all parties to the conflict in Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado Monthly: March 2021 - ACLED (ACLED, 2021)
In This Report: Analysis of the IS claim of the Palma attack in the context of the overall relationship between IS and the Cabo Delgado insurgency Discussion of growing tensions between displaced people, host communities, and aid organizations in districts with growing displaced populations Update on international involvement in the Cabo Delgado conflict and analysis of the role that South African companies Dyck Advisory Group and Paramount Group play in the conflict
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Ten Conflicts to Worry About in 2021 (ACLED, 2021)
A review of key developments in 2020 with a look toward trends to watch in the coming year.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: How Total plans to protects its $15bn major gas project - Le Bec, Christophe (The Africa Report.com, 2021)
Total is going ahead with its Mozambique LNG project despite a major armed insurgency in Cabo Delgado. This article discusses plans to secure its Afungi facility, including security forces involved. Facility employment is projected to triple by 2022, from 5,000 in 2020 to 15,000 by 2022.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; employment / emprego; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Humanitarian Response Plan Mozambique (United Nations Office for the Coordination of Humanitarian Affairs (OCHA), 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Mozambique LNG Project Could Be Transformational For Mozambique — If Western Environmentalists Don’t Interfere | Africa Oil & Power (2020)
NJ Ayuk discusses the Mozambique LNG project.
Section: Interviews
Keywords: #Reporting & Media / Reportagem & Mídia; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; private sector / setor privado

Total signs agreement with the Government of Mozambique regarding the security of Mozambique LNG project (Total.com, 2020)
Map Mozambique
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; private sector / setor privado

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Broadening the Analysis of Peace in Mozambique: Exploring Emerging Violence in Times of Transnational Extractivism in Cabo Delgado - Alberdi, Jokin; Barroso, Manuel (Global Society, 2020)
This article explores the contemporary expressions of violence and oppression linked to the action of the extractive industry in the northern province of Cabo Delgado, Mozambique. Twenty-five years after the signing of the General Peace Agreement, the debate on peace in the country has remained confined to the resurgence of armed clashes between RENAMO combatants and State security forces in recent years. It is proposed here, however, that the current range of violence that challenge peace in Mozambique is broader and more diverse, requiring an analysis that considers the arrival of transnational extractivism. This study, taking Cabo Delgado province as a case-study, aims to broaden the scope of academic debates by establishing a dialogue with the practice of local peacebuilding, and contributions from the critical political economy of development and the collective capability approach.
Publisher: Routledge _eprint: https://doi.org/10.1080/13600826.2020.1772730
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; extractive industries / indústrias extractivas

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Face ao conflito no norte, o que Moçambique pode aprender da sua própria guerra civil (1976 – 1992)?: Uma análise das dinâmicas da insurgência em Cabo Delgado - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Analisa as dinâmicas da insurgência em Cabo Delgado e procura interrogar o que Moçambique pode aprender dos seus ciclos de violência armada, particularmente a guerra civil, para fazer face ao actual conflito no Norte do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Desenvolvimento socioeconómico de Cabo Delgado num contexto de conflito - João Feijó; António Souto; Jerry Maquenzi (Observador Rural, 2020)
Um conjunto de contradições internas e de longa duração estruturam as relações socioeconómicas na província, estando em grande medida na origem da conflitualidade actual. Não obstante a crescente interferência de factores externos na dinamização do conflito, os dados disponíveis permitem-nos concluir que, enquanto persistirem elementos internos de contradição, não será possível encontrar uma solução sustentável para o conflito. Não obstante o conflito implicar, inevitavelmente, uma intervenção militar, para prover a segurança das populações e de bens, as profundas contradições internas existentes obrigam à realização de um plano de desenvolvimento social e económico, entendido como a melhor estratégia de contra-insurgência, limitando o alastramento do conflito armado por outras zonas da província marcadas pela pobreza e por históricas relações de protesto em relação ao Estado. Uma vez que as informações são escassas e imprecisas e a situação militar no terreno é bastante imprevisível, torna-se difícil definir linhas gerais para um plano de intervenção. Não obstante, neste documento pretende-se apresentar um conjunto de elementos que devem ser considerados, de forma coerente, na implementação de qualquer projecto de desenvolvimento, distinguindo as diferentes áreas socioeconómicas de intervenção na província de Cabo Delgado, em função da realidade actual.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict / conflito; economic development / desenvolvimento económico

Protecção social em contexto de terrorismo: que implicações tem a insurgência islâmica nos mecanismos formais de protecção social em Moçambique? - Siúta, Moisés (2020)
O impacto do terrorismo em Moçambique é uma realidade que não se restringe apenas à zona Norte do país. O IDeIAS nº 137, da autoria de Moisés Siúta, procura discutir as suas implicações nos sistemas formais de protecção social tendo em conta o desafio que enfrentam de garantir protecção e bem-estar social da população nas regiões mais afectadas sem, no entanto, deixar para trás a população vulnerável a diversos riscos como seca, cheias e a pandemia.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito; social protection / proteção social; ⛔ No DOI found

Geografia Eleitoral e Insurgência em Cabo Delgado - Brito, Luís de (Desafios para Moçambique, 2020)
This chapter looks at the origins of the extremist insurgency in Cabo Delgado and posists that to understand its origins, we must look beyond religious extremeism and to other factors in order to analyse the situation from difference perspectives. This study looked at electoral data in Cabo Delgado to determine if there is a relationship bwtween voting patterns, including abstention, and political cleavages and social conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; electoral geography / geografia eleitoral

Ugandenses e Tanzanianos do Al-Shabaab: um olhar à dimensão internacional do conflito em Cabo Delgado - Chichava, Sergio (Desafios para Moçambique, 2020)
O conflito militar que, desde 5 de Outubro de 2017, se abate sobre Moçambique, com particular incidência na província de Cabo Delgado e protagonizado por um grupo localmente conhecido por Al-Shabaab, cuja pretensão é substituir o Estado laico por um Estado regido pela Sharia, tem sido regularmente descrito pelas autoridades moçambicanas como tendo, além de uma dimensão interna, uma componente externa. Desde o início do conflito, as autoridades locais falam da prisão ou da procura de vários estrangeiros que estariam a treinar, financiar e dirigir a «insurgência» em Cabo Delgado com vista a retardar o desenvolvimento do País e a explorar ilegalmente diversos recursos naturais. De entre os diversos estrangeiros frequentemente mencionados, o destaque vai para tanzanianos e ugandenses. Por seu turno, o Al-Shabaab tem vindo a reclamar uma dimensão internacional, declarando fidelidade ao Estado Islâmico (EI) ou Daesh. Ao que tudo indica, o Daesh também reconhece o Al-Shabaab, que designa por «soldados do Califado» pertencentes ao Estado Islâmico da Província da África Central (ISCAP, no acrónimo inglês), uma região cujos contornos geográficos ainda não estão bem claros, mas que englobaria actualmente, além Moçambique, a República Democrática do Congo (RDC), País onde está baseado o grupo islamista ugandês Forças Democráticas Aliadas (ADF), que também tem sido apresentado nalguns fóruns como tendo relações com o Al Shabaab em Moçambique, através da presença de alguns dos seus militantes neste País, ou através do recrutamento e treino de jovens moçambicanos na RDC. Com base nos elementos acima, o objectivo deste texto é fazer uma breve análise da componente internacional do AlShabaab, olhando para a sua ligação com a Tanzânia, o Uganda e o EI. Mais precisamente, olhando para o perfil dos cidadãos ugandeses e tanzanianos que têm sido referenciados como sendo do Al-Shabaab, o texto procura responder às seguintes questões: quem são os tanzanianos e ugandeses do Al-Shabaab? Como chegaram a Moçambique? O que pretendem? Porque escolheram a província de Cabo Delgado? Será o Al-Shabaab uma filial do Estado Islâmico? Para responder a estas questões, primeiro apresenta-se o perfil dos tanzanianos e ugandeses do Al-Shabaab; a seguir, apresentam-se algumas hipóteses sobre as suas pretensões; e, por último, abordam-se alguns elementos sobre a possível ligação do Al-Shabaab ao Daesh ou ao EI.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
978-84-09-17639-7
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, João (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
ISBN: 9782490093182 OCLC: 1199064112
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Face ao conflito no norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgago - Forquilha, Salvador; Pereira, João (Desafios para Moçambique 2020, 2020)
A história de Moçambique dos últimos 50 anos tem sido marcada por ciclos de violência armada de contestação ao Estado, não só colonial, como também pós-colonial. Com efeito, desde a guerra anticolonial levada a cabo pela Frente de Libertação de Moçambique (Frelimo), passando pela guerra civil, que opôs a Resistência Nacional Moçambicana (Renamo) ao Governo da Frelimo, até às crises político-militares pós-eleitorais, a violência armada tem estado presente no processo da construção do Estado em Moçambique. No início de Outubro de 2017, começou uma outra contestação violenta ao Estado na província de Cabo Delgado. No dia 5 de Outubro de 2017, um grupo de homens armados atacou as instituições do Estado na vila sede de Mocímboa da Praia. Inicialmente associado a um banditismo de mera perturbação da ordem pública, o fenómeno ganhou rapidamente proporções alarmantes. Os ataques começaram a multiplicar-se. Dois meses depois do primeiro ataque, a Polícia já havia detido 251 suspeitos, dos quais 37 eram cidadãos de nacionalidade tanzaniana (O País, 2017). Em Dezembro de 2017, a Polícia da República de Moçambique, ao mais alto nível, esteve na zona e visitou os distritos de Mocímboa da Praia e Palma. No comício popular que realizou na vila sede de Mocímboa da Praia, o Comandante Geral da Polícia, Bernardino Rafael, deu um «ultimato» aos atacantes de Mocímboa da Praia, decretando sete dias para se entregarem às autoridades (O País, 2017). No entanto, a violência continuou e, nas semanas e meses que se seguiram ao ataque à vila sede de Mocímboa da Praia, a situação de segurança piorou no terreno e os ataques espalharam-se para outros distritos da zona norte de Cabo Delgado. Entre finais de Março e meados de Abril de 2020, a violência armada atingiu níveis nunca vistos antes, com o assalto e a ocupação temporária de quatro vilas nos distritos de Mocímboa da Praia, Quissanga, Muidumbe e Ibo. Que factores estão na origem do avanço da insurgência no terreno? Que tipo de relação se vai desenvolvendo entre os insurgentes e as populações locais? Existe algum potencial para que a insurgência se alastre para o Sul, em direcção à zona costeira de Nampula? Como tem vindo o Estado a responder à insurgência? Estas perguntas são uma parte importante do programa de pesquisa intitulado «Estado, violência e desafios de desenvolvimento no Norte de Moçambique», em curso no IESE desde Agosto de 2019.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Delgado e o Risco Sistémico da Guerra em Moçambique - Ngoenha, Severino; do Amaral, Giverage; Nhumaio, Alcido (Desafios para Moçambique 2020, 2020)
Em Moçambique a guerra é um risco sistémico: na linguagem de Thomas Hobbes, é a mãe de todos os riscos. A guerra é transversal a todos os outros riscos em termos de consequências sociais, económicas, políticas e culturais: destrói as infra-estruturas, como a rede escolar, os hospitais, as vias de acesso e os tecidos sociais; enfraquece a economia; paralisa a agricultura; apodera-se da indústria; e instala a fome, a miséria e toda a espécie de desgraças. A guerra é o maior dos riscos sistémicos de Moçambique não apenas pelos seus efeitos altamente destrutivos, mas porque agrava a probabilidade de ocorrência dos demais riscos aos quais o País está sistemática e concomitantemente exposto. Em geral, as considerações sobre a guerra em Moçambique são feitas de duas maneiras diferentes. De um lado, a abordagem político-militar, que privilegia a busca de mecanismos de diálogo entre os beligerantes, o que supõe o conhecimento e o reconhecimento entre as partes e das razões que levam uns e outros a optar por um confronto armado. Esta abordagem tem sido a adoptada pelos diferentes governos moçambicanos que enfrentaram conflitos nos seus mandatos, ou seja, todos. Actualmente não parece que uma tal via se vislumbre salutar nas estratégias contra os dois conflitos armados em curso no Centro e Norte do País. Por outo lado, a abordagem técnico-científica, que parte do pressuposto de que o fenómeno da guerra é complexo e privilegia uma epistemologia interdisciplinar, na qual participam muitos saberes disciplinares no esforço de apreender as suas razões e causas. Esta abordagem procura entender o que leva o País a fazer da guerra o seu modus vivendi, o que leva grupos, partidos e facções militares a optarem sistematicamente pela confrontação militar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

O Cabo do Medo - O Daesh em Moçambique 2019-2020 - Rogeiro, Nuno (UCCLA, 2020)
Toda a verdade sobre a situação explosiva do domínio do Norte de Moçambique pelo Daesh. É o primeiro livro a nível mundial que revela em primeira mão o que se está a passar na zona de Cabo Delgado: a conquista e subjugação das populações, a violência bárbara com recurso a decapitações e execuções sumárias, a exploração das pessoas e dos recursos disponíveis, a impotência das autoridades moçambicanas em impor a ordem e a paz social. Um livro de grande acualidade que desvenda uma realidade tão chocante quanto desconhecida. “Uma análise exaustiva da ocupação desta terra boa (nordeste de Moçambique), de gente boa, pelo Daesh. Tem de ser combatido mas, primeiro, tem de ser compreendido.” Nuno Rogeiro
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Publisher: Institute for Security Studies (ISS)
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Coesão social e violência política em Moçambique: notas para debate - Forquilha, Salvador; Gonçalves, Euclides (2019)
Perguntas e método de pesquisa Contexto: • Dados da primeira fase de uma pesquisa programática no norte de Moçambique Pergunta: • Como operacionalizar operacionalizar a noção de coesão social em Moçambique? • Que subsídios a noção de coesão social pode oferecer para a compreensão da violência política em Moçambique? Recolha de dados • Período: Abril e Maio de 2019 • Locais: Cidade de Maputo, Chiúre (Cabo Delgado), Chimbunila (Niassa) e Mussuril (Nampula) • Entrevistas: Representantes e membros de partidos políticos, líderes comunitários e religiosos, grupos de camponeses e jovens • Análise de dados: Mapeamento de factores com potencial para conflicto (conflict mapping)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Tanzaniano recruta jovens no Niassa para ataques em Cabo Delgado - Governo de Moçambique (Governo de Moçambique, 2019)
Alguns jovens do distrito de Mecula, no Niassa, norte de Moçambique, são recrutados para integrarem o grupo de malfeitores que protagonizam ataques armados nos distritos do norte da vizinha província de Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Niassa; L - portuguese / português; youth / juventude

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Radicalização Islâmica No Norte De Moçambique: O Caso Da Mocímboa Da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (2018)
Contextualização da pesquisa: - No dia 5 de Outubro de 2017, um grupo de homens armados, aparentemente com motivações religiosas, ataca instituições do Estado (postos policiais) na Vila da Mocímboa da Praia; - Rapidamente, o assunto da radicalização islâmica no norte de Moçambique passou a chamar a atenção do Governo, sector privado, sociedade civil, parceiros de cooperação, analistas, comentadores, cidadãos comuns, etc. - Para muita gente, as perguntas comuns eram: De onde vem esse grupo da Mocímboa da Praia? Existe fundamentalismo islâmico em Moçambique? Não são homens da Renamo disfarçados de fundamentalistas islâmicos? - Foi neste contexto que o IESE e o MASC decidiram realizar uma pesquisa exploratória como preparação para uma pesquisa mais aprofundada.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Livelihood Interventions and Biodiversity Conservation in Quirimbas National Park - Chevallier, Romy (South African Institute of International Affairs (SAIIA), 2018)
Coastal livelihood interventions can help communities by providing additional incomes, while protecting and maintaining resources and the environment. The identification and promotion of resilient and diversified livelihood opportunities are crucial to enhance communities’ adaptive capacity to respond to the multiple stresses and shocks in a changing coastal environment. Coastal livelihood opportunities are especially important in their support for biodiversity conservation in and around protected areas. Quirimbas National Park (QNP) in Mozambique has some of the greatest marine biodiversity in the region and is one of the country’s largest and most important protected areas. This policy insight considers the most appropriate livelihood-focused interventions for coastal communities in the QNP, taking account of past and current project experiences. In areas where communities and park officials need additional support, it makes recommendations on how to best enhance initiatives.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources / recursos naturais

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Falta de alimentos agrava-se em zonas atacadas na província de Cabo Delgado - Macuácua, Amandio Roberto (Jornal Notícias, 2018)
A falta de alimentos está a agravar-se em zonas do interior na província de Cabo Delgado por causa dos ataques causados por grupos armados que têm levado a população a abandonar terras, alerta um relatório ontem divulgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Perfil Do Distrito De Macomia Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Macomia; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza

A Rede de Negocios da Frelimo no Norte - , Erik (Verdade - A verdade a cada palavra, 2013)
O investimento em energias e infra-estruturas pode transformar o negligenciado norte e afectar a sucessão presidencial. Andarko e outras companhias petrolíferas prevêem que o gás descoberto em Cabo Delgado pode duplicar o produto interno bruto anual. Por enquanto acredita-se que as vastas reservas de carvão se encontram na província do Niassa. O centro de gravidade de oportunidades económicas de Moçambique parecem se transladar para o norte. O governo está a atrair investidores estrangeiros para ajudarem na transformação desses recursos naturais em rendimentos públicos para o que era até agora um dos países mais pobres do mundo.
Keywords: #Reporting & Media / Reportagem & Mídia; G - north / norte; GP - Cabo Delgado; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Relatório para o Governo da Província de Cabo Delgado e Agência Espanhola de Cooperação Internacional para o Desenvolvimento (AECID) - Umarji, Mariam; Makda, Sadya; Paulo, Arsénio; Lalá, Aly (SAL & Caldeira, 2009)
O relatório que se segue retrata a avaliação conduzida ao Sistema de Gestão de Finanças Públicas da Província de Cabo Delgado considerando o ciclo orçamental do ano de 2008, considerando a informação de contabilidade, reporte e auditoria relacionada com este ano mas produzida em 2007 e em 2009. A avaliação teve como base a Metodologia PEFA – Despesa Pública e Responsabilidade Financeira – devidamente adaptada ao nível subnacional (província) de acordo com as orientações metodológicas emanadas pelo Secretariado PEFA. Foram utilizados um total de 25 indicadores para a avaliação. Os indicadores reflectem a situação actual do sistema e fornecem um ponto de comparação para avaliações ou seguimentos futuros dos progressos esperados nos processos de planificação, orçamentação, contabilidade, reporte e auditoria da província. Esta Avaliação Sumária apresenta as constatações finais da equipa de consultores sendo fruto do trabalho de campo realizado para inquérito e recolha de evidência combinada com a revisão documental de informação recebida e disponibilizada de forma a se poder realizar a avaliação dos diferentes indicadores.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; budget / orçamento; fiscal policy / política fiscal

Muslims of northern Mozambique and the liberation movements - Bonate, Liazzat J. K. (Social Dynamics, 2009)
Despite the fact that the liberation war occurred in northern Mozambique, where a considerable number of Muslims lived, their contribution to the independence struggle has been little studied. This paper focusses on their participation in two nationalist liberation movements, Mozambican African National Union (MANU) and Frente de Libertação de Moçambique (FRELIMO), and demonstrates that the prevailing idea in scholarship about Muslims’ aloofness from the liberation struggle is unjustified. It argues that Muslim support and participation in the liberation movements stemmed primarily from grassroots African nationalism. Like most Africans, Muslims wished to end colonialism and recover their land from the Portuguese. African Muslims of northern Mozambique were well suited to support these movements, because Islam and chieftainship were linked to each other. Chiefs were believed to be the ‘owners’ and ‘stewards’ of the land, and a majority of Muslim leaders, whether traditional chiefs (régulos, in Portuguese) or Sufi leaders (tariqa khulafa’, in Arabic), were from the chiefly clans. Most importantly, Muslims of northern Mozambique had close historical and cultural ties to Tanganyika and Zanzibar, especially through Islamic and kinship networks. The involvement of Muslims in the liberation movements of those regions, in particular in Tanganyika African National Union (TANU), inspired and encouraged the Muslims of northern Mozambique to support MANU and FRELIMO, especially since these two movements were launched in Tanganyika and Zanzibar with TANU backing and the participation of Muslim immigrants from northern Mozambique.
Publisher: Routledge _eprint: https://doi.org/10.1080/02533950903076378
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito